Improve Students' Description Text Writing Skills using Higher Order Thinking Ability-Based Learning - Nuraeni, Nuraeni; Syahruddin, Syahruddin; Ratnawati, Ratnawati (Institut Agama Islam Negeri Palopo, 2023)
Students' limited descriptive writing skills can hinder their ability to express ideas clearly, expand their vocabulary, and develop their imagination. This, in turn, may restrict their communication skills when conveying experiences or concepts in a detailed and structured manner. This study seeks to examine the impact of higher-order thinking skills-based learning on students' descriptive writing abilities in the context of Indonesian language education, potentially offering valuable insights into effective learning strategies. The research employed a quasi-nonequivalent control group experimental design, dividing junior high school students into two balanced groups. The experimental group, consisting of 35 students, utilised higher-order thinking Ability Based Learning, while the control group, also comprising 35 students, did not. The study encompassed the entire population of seventh-grade students, totalling 70 individuals. Data collection involved observation, tests, and documentation, with analysis conducted using Descriptive Statistics and Inferential Statistics via the SPSS application. The findings indicate a significant positive impact of higher-order thinking skill-based learning. Students who engaged in this approach demonstrated substantial improvement in their descriptive writing skills, enhancing their capacity to critically analyse information, think creatively, and solve problems.